Improving Students’ Oral Communication Skills in Public Speaking through Individual Presentation Task - Ahmad Burhanuddin (Jurnal Lingua Idea, 2021)
This current study attempts to seek the answers of a question: how effective is the individual presentation method in improving students' oral communication skills, especially in public speaking? Designed as a qualitative research, this research was conducted at the Faculty of Tarbiyah and Teacher Training of IAIN Pekalongan in the academic year of 2019/2020. The research involved 100 of the second year students of the English Education Department of IAIN Pekalongan who took Public Speaking course. The data were collected through an open-ended questionnaire as the instruments of this study to get their perception after taking the course with performing an individual presentation as its main task. The research findings reveal despite the obstacles they encountered, the presentation task was effective to enhance students’ confidence as well as to give them experience to speak in front of a crowd. The task also gave them more awareness and self-evaluation on how to perform a good public speaking as they received direct feedback from the audience while performing the individual presentation.